The Impact of COVID-19 on Preventive Oral Health Care During Wave One - Meyer, Beau D.; Danesh, David O. (Frontiers in Dental Medicine, 2021)
Introduction: Early childhood caries burdens children, their families, and the health care system. Utilizing fluoride varnish at medical well-child visits with non-dental primary care providers can be an interprofessional strategy to combat early childhood caries. However, the COVID-19 pandemic dramatically altered preventive health care delivery and the effects on preventive oral health care delivery have not been previously described. Methods: This analysis used descriptive statistics and non-parametric Wilcoxon Mann-Whitney tests to compare preventive oral health utilization among 1- to 5-year old children in two state Medicaid agencies before and during the pandemic. Fluoride utilization rates at dental visits and medical well-child visits was calculated as number of users per 1000 enrolled children. Additionally, the proportion of well-child visits that included fluoride application was calculated for each state. Results: During the pandemic, fluoride utilization rate decreased at dental visits (pre-pandemic=153.5 per 1000 enrolled children; pandemic=36.1 per 1000 enrolled children; p<.001) and decreased at medical well-child visits (pre-pandemic=72.2 per 1000 enrolled children; pandemic=32.3 per 1000 enrolled children; p=.03) significantly decreased during the pandemic. However, the proportion of well-child visits that included fluoride application did not significantly change (pre-pandemic=26%; pandemic=20%; p=.2). Conclusions: The findings highlight the importance of interprofessional collaboration among non-dental primary care providers and dental providers to provide access to preventive oral health services, particularly when access to dentists is limited. Future directions might include rigorous evaluations of co-located medical and dental services or the use of interprofessional telehealth technologies.